2006
DOI: 10.1111/j.1468-3083.2006.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and functionality of silver‐coated textiles in patients with atopic eczema

Abstract: In conclusion, silver-coated textiles are able to improve objective and subjective symptoms of AE significantly within 2 weeks, showing a good wearing comfort and functionality comparable to cotton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 31 publications
(42 reference statements)
0
27
0
1
Order By: Relevance
“…Today, metallic silver and silver compounds are predominantly used in antibacterial fabrics by contrast with other biocides, that is, in sport and leisure wear as well as in fabrics for the treatment of atopic dermatitis [3, 68, 11]. As the use of silver products increases, it is becoming more important to develop standard procedures to measure the efficacy of each product in order to discuss questions concerning comparability, mechanisms and risks [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, metallic silver and silver compounds are predominantly used in antibacterial fabrics by contrast with other biocides, that is, in sport and leisure wear as well as in fabrics for the treatment of atopic dermatitis [3, 68, 11]. As the use of silver products increases, it is becoming more important to develop standard procedures to measure the efficacy of each product in order to discuss questions concerning comparability, mechanisms and risks [21].…”
Section: Discussionmentioning
confidence: 99%
“…Many lines of evidence suggest a role for microorganisms in noninfectious skin diseases, such as atopic dermatitis, rosacea and acne [33, 34] Therefore, antiseptic therapies using liquid skin disinfectants and systemic antimicrobials are essential for the efficient dermatotherapy of affected lesions of atopic dermatitis patients [3]. Hartmann [35] has shown that liquid antimicrobials may have a short-term impact on the ecosystem of the skin flora, a view which is supported by our results taken with the antibacterial silver deodorant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gauger and colleagues 343 in Germany compared Padycare ® (TEXAMED ® GmbH), a polyamide and LYCRA ® (INVISTA, Wichita, KS, USA) material with silver filaments woven in to produce a silver content of 20% in total, with a cotton textile. Both were worn day and night for 2 weeks as either an all-in-one suit for infants or a long-armed and long-legged suit.…”
Section: Harmsmentioning
confidence: 99%
“…10,11 To identify RCTs published prior to the CLOTHES trial, we searched the Global Resource of Eczema Trials database. 12 At the time of starting the CLOTHES trial, 14 small RCTs assessing the effects of therapeutic clothing had been published: three RCTs investigated silk clothing [DermaSilk TM (AlPreTec Srl, San Donà di Piave, Italy)]; [13][14][15] two investigated silver-coated textiles; 16,17 three investigated cellulose seaweed fibres with silver; [18][19][20] one investigated cellulose; 21 one investigated an anion textile; 22 two investigated types of ethylene vinyl alcohol fibre; 23,24 one investigated borage oil-coated garments; 25 and one investigated cotton and synthetic fibres. 26 Since the start of the trial, an additional study on chitosan-coated textiles has been published.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%